Quality And Palatability Level Of Rami Waste Silage In Garut Sheep - Ruly Budiono; Joko Kusmoro; Asep Z. Mutaqin; Alif K. Sutomo (International Journal of Quantitative Research and Modeling, 2026)
Silage is an alternative livestock feed in the form of fermented forage that is stored for long periods in anaerobic conditions and can meet the availability of forage for livestock during the dry season. The objective of this study was to obtain a high-quality ramie waste (Boehmeria nivea) silage formulation with the best palatability for sheep based on the feed intake of Garut sheep on ramie silage and the best quality based on storage life. This study used 6 male Garut sheep aged 12-16 months with an average weight of 32 kg. The sheep were given 4 treatments, namely P0 = Rami leaf silage without additives (as basal feed); P1 = Ramie leaf silage, rice bran, and 0.5% aromatic bran; P2 = Ramie leaf silage, rice bran, 0.5% aromatic bran, and 5% molasses; P3 = Ramie leaf silage, rice bran, and 1% aromatic bran. The study was conducted using a completely randomized design (CRD), and each sheep was placed in an individual pen. The research data were processed using analysis of variance, then to determine the differences between treatments, it was followed by Duncan's multiple range test. The results showed that the physical quality of the silage was still in good condition up to 9 months of ensilage and could be used as a solution to feed shortages in the future. This can be seen from the level of palatability of Garut sheep to flax waste silage >50% measured from the average daily consumption of livestock.